Potencial de Aspergillus niger para biocontrole de patógenos fúngicos de solo - Rocha, Larissa Lara (2021)
The need to increase the productivity of agricultural crops in a sustainable way, combined with environmental preservation, is a challenge for modern agriculture. Regarding the control of root diseases, which cause negative environmental impacts due to the intensive use of fungicides, one of the strategies studied to overcome this challenge is the introduction of antagonistic microorganisms for biological control of pathogens. Aspergillus niger has characteristics beneficial to plant growth and, therefore, has potential for inoculants development. Thus, the objective of this work was to evaluate in vitro biocontrol potential of A. niger on the following soil pathogens: Fusarium oxysporum, Fusarium solani, Macrophomina phaseolina, Rhizoctonia solani, Sclerotinia sclerotiorum, Sclerotium cepivorum and Sclerotium rolfsii. The biocontrol potential of two A. niger strains (ATCC 1015 and FS1) was evaluated using the methods of paired cultivation, production of volatile metabolites and production of thermostable metabolites. In paired culture, F. oxysporum, F. solani and R. solani showed inhibition percentages above 45% and there was no significant difference between A. niger strains. Possible volatile metabolites secreted in the medium by the strains reduced the growth of S. cepivorum, S. rolfsii and F. oxysporum. Growth inhibition by thermostable metabolites was detected only in M. phaseolina exposed to metabolites fromstrain ATCC 1015. The results of this work indicate the potential of A. niger for biocontrol of the fungi F. oxysporum, F. solani, R. solani S. cepivorum, S. rolfsii and M. phaseolina.